2022
DOI: 10.1093/tropej/fmac037
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Bronchopulmonary Dysplasia in 625 Neonates with Respiratory Distress Syndrome

Yue Tao,
Xiao Han,
Wan-Liang Guo

Abstract: Objective This study was designed to investigate the predictors of bronchopulmonary dysplasia in neonates with respiratory distress syndrome. Methods This was a single-center retrospective cohort study conducted between 1 January 2015 and 31 December 2020. A total of 625 neonates with respiratory distress syndrome (RDS) were enrolled. Demographic data, clinical presentations, complications and related treatment information were collected and analyzed. We used bivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…A total of 1,011 articles were retrieved from the databases using systematic and manual searches. After removing the duplicates, and performing screening of abstracts and full-text articles, 21 studies (5,15,16,19,20,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) were included. These studies included a total of 6,567 control infants and 1,476 patients with BPD, and were eligible for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,011 articles were retrieved from the databases using systematic and manual searches. After removing the duplicates, and performing screening of abstracts and full-text articles, 21 studies (5,15,16,19,20,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) were included. These studies included a total of 6,567 control infants and 1,476 patients with BPD, and were eligible for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Infants with lower birth weight (BW) and gestational age (GA) are at risk for developing BPD. In addition, maternal smoking, chorioamnionitis, male sex, oxygen therapy, duration of mechanical ventilation, and co-morbidities, including sepsis, necrotizing enterocolitis, and pulmonary hemorrhage have been found to be associated with BPD (3)(4)(5). Epidemiological studies have reported that approximately 80% of preterm infants born between 22 and 24 weeks of gestation will develop BPD to a certain degree (6).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria included the following: (1) very preterm infants (<32 wk of gestational age) with a very low birth weight (<1500 g for birth weight); (2) preterm infants with BPD risk factors [27][28][29][30], such as <28 wk of gestational age, undergoing continuous mechanical ventilation (MV), non-invasive respiratory support with FiO 2 > 0.3 and a positive end-expiratory pressure of >6 cmH 2 O, or continuous respiratory support with hemodynamically significant patent ductus arteriosus (hsPDA) or sepsis at 7-10 days of life; and (3) written informed parental consent was required.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…AECIIs, as the stem cells of the alveolar epithelium, exhibit a physiological state closely linked to lung injury occurrence and restoration of damaged alveolar epithelium morphology and function following hyperoxia exposure. Nonetheless, on the condition that exposed to numerous inflammatory factors, AECII structure becomes compromised, preventing its self-repair and hampering migration and differentiation into AECIs [3,4]. Hyperoxia induces the activation of macrophages in immature lung tissues, resulting in the release of interleukin-6 (IL-6), interleukin-17 (IL-17), and regulatory chemokines [5].…”
mentioning
confidence: 99%